Firm Level Implications of Early Stage Venture Capital Investment: An Empirical Investigation - Max Keilbach; Dirk Engel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
The paper analyses the impact of venture capital finance on growth and innovation activities of young German firms. Among other variables, our panel of firm data includes data on venture capital funding and patent applications. With a statistical matching procedure we draw an adequate control group of non venture funded firms. The analysis gives evidence that innovative firms will be able to close a venture capital deal with higher probability. Once the firms are venture funded, they display higher growth rates but do not differ in their innovative output from otherwise comparable firms. We derive strategic implications.
Keywords: L21; D21; C33; D92; C14; 330; Firm Demography; Firm Start-Ups; Firm Growth; Venture Capital; Patented Inventions; Microeconometric Evaluation Methods; Risikokapital; Unternehmensgründung; Innovation; Unternehmenswachstum; Schätzung; Deutschland